Jebakan dalam memilih pasangan hidup - Goei, Yonathan Aditya (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2015)
All people who get married want to have a happy marriage and they find a partner that can fulfill their dream. However, statistic showed that divorce rate is increased, along with the declined level of marital satisfaction, which give indication that there may be something wrong in the process of finding a partner. The author discussed why attraction goes awry, the influence of family background and traits of people who tend to make mistake and lastly how to solve this problem.